RISKS AND HAZARDS DIAGNOSTICS OF IMPACT OF INDUSTRY-RELATED LANDS UNDER MUNICIAL SOLID WASTE LANDFILLS ON FARMLANDS - Sereda, M. S. (Scientific Progress & Innovations, 2021)
The problem of municipal solid waste (MSW) handling is extremely topical for the regions of Ukraine. Landfills occupy valuable farmland resources and pollute them, cause damage and losses to the environment and agriculture. Therefore, the purpose of our studies became forming the methodological bases of MSW landfills classification by the level of hazard for the adjoining areas with the aim of further selecting the method of these territories’ improvement. It has been determined that the main threats of industry-related disturbed lands under MSW landfills are the following: the hazards of environmental and sanitary-hygienic nature; the hazards of economic and food nature; the threats of resource nature. Proceeding from the reason and consequence relation of the existing hazards of the impact of industry-related lands under MSW waste deposits on farmlands, a complex of indicators was developed which characterize the level MSW danger for the adjoining areas, the boundaries of assessing the level of MSW landfills’ hazards for these territories by the integral mark were determined. Based on the conducted estimation of the level of MSW landfills’ danger for the adjoining areas on the example of Poltava region, it has been established that 40% of the total num-ber of MSW dumps are in the zone of pre-crisis condition; 53% are in the zone of crisis condition; and 7% of the total number are in the zone of critical condition. Taking into account that the majority of MSW landfills are located at a distance of less than 200 m away from farmlands (93%) and have pre-crisis, crisis or critical level of hazard for the adjoining areas, the unsolved problems in this sphere pose danger for the environmental and food security of these territories and sustainable development of agro-ecosystems. The implementation of the methodological approach enables to evaluate the level of MSW landfills’ hazard for the adjoining areas of development, determine the main dangers and risks for farmlands located in the zone of MSW waste deposits’ impact, and the di-rections to overcome them. Practical application of the developed methodology is possible within the framework of the program-target method while working out and implementing the national and regional programs, directed at improving the process of management of MSW handling sphere.